1996
DOI: 10.1007/bf02275535
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction following rhinoplasty

Abstract: This retrospect study was conducted to evaluate patients satisfaction following rhinoplasty. Of the 1,062 patients who had undergone rhinoplasty and received a questionnaire, there were 468 respondents. They rated satisfaction with aesthetic and functional results of the surgery. Four groups were created: Group I comprised all the respondents: 468 patients of which there were 381 (81.4%) females and 87 (18.6%) males; 6.2% of this group was dissatisfied. Group II [373 patients: 301 (80.7%) female and 72 (19.3%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
1
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 4 publications
0
53
1
7
Order By: Relevance
“…Certain factors can influence patient satisfaction, like his/her culture, life experience, and chiefly his/her level of expectations about the outcome, which may or may not be realistic [10,12]. Therefore, it is important for the surgeon to understand the patient's complaints and then to analyze the proportions and ratios between the nose and face through a physical examination.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Certain factors can influence patient satisfaction, like his/her culture, life experience, and chiefly his/her level of expectations about the outcome, which may or may not be realistic [10,12]. Therefore, it is important for the surgeon to understand the patient's complaints and then to analyze the proportions and ratios between the nose and face through a physical examination.…”
Section: Discussionmentioning
confidence: 98%
“…Several surveys were performed aimed at validating a reliable questionnaire to be answered by patients who underwent cosmetic surgery with the purpose of measuring patient satisfaction postoperatively [5][6][7][8][9][10]. Questionnaires that evaluate quality of life and self-image became the gold standard and eventually replaced the simplistic form by which patients were asked whether they had noticed any improvement after rhinoplasty [11,12].…”
mentioning
confidence: 99%
“…This is in accordance with previous research, where authors reported neglected anatomic problems inside the nose becoming the source of nasal symptoms after surgery leading to postoperative dissatisfaction and revision RP. 1,5,13 Mucosal disease was present in 28% of RP patients; in 36 patients (13% of RP patients) sensitization to commonly inhaled allergens was diagnosed. The negative influence of nasal mucosal disease on quality of life has been extensively documented.…”
Section: Discussionmentioning
confidence: 99%
“…En matière de rhinoplastie, le chiffre de l'insatisfaction des patients après révision(s) varie de 5 à 10 % selon les séries [1][2][3][4].…”
Section: Introductionunclassified